Adaptive slip ratio estimation for active braking control of high-speed trains. (June 2021) - Chen, Bin; Huang, Zhiwu; Zhang, Rui; Jiang, Fu; Liu, Weirong; Li, Heng; Wang, Jing; Peng, Jun
Abstract: Active braking control systems in high-speed trains are vital to ensure safety and are intended to reduce brake distances and prevent the wheels from locking. The slip ratio, which represents the relative difference between the wheel speed and vehicle velocity, is crucial to the design and successful implementation of active braking control systems. Slip ratio estimation and active braking control are challenging owing to the uncertainties of wheel–rail adhesion and system nonlinearities. Therefore, this paper proposes a novel adaptive slip ratio estimation approach for the active braking control based on an improved extended state observer. The extended state observer is developed through the augmentation of the system state-space to estimate the unmeasured train states as well as the model uncertainty. The accurate slip ratio is estimated using the observed extended states. Furthermore, the adaptability of the observer is improved by introducing the beetle antennae search algorithm to determine the optimal observer parameters. Finally, a feedback linearization braking control law is established to stabilize the closed-loop system due to its potential in coping with nonlinearities, which benefits the proven theoretical bounded stability. Experimental results validate the effectiveness of the proposed method. Highlights: An active braking control method based on an improved extended state observer is proposed for high-speed trains. The designed observer is utilized to estimate both the slip ratio and train adhesion. The adaptability of the extended state observer is improved by introducing the beetle antennae search algorithm to optimize its parameters. A feedback linearization braking control law is established to counteract the system nonlinearity and uncertainty.